ANALISIS GAYA KEPEMIMPINAN DAN PEMBERIAN KOMPENSASI DALAM MENINGKATKAN KINERJA KARYAWAN THE CLINIC BEAUTYLOSOPHY MEDAN - Yuliani, Nur Irma; Siregar, Onan Marakali (Transpublika Publisher, 2023)
This study aims to determine how leadership style and compensation in improving employee performance. This study uses a qualitative approach. Direct researchers act as the primary research tool, which carries out the research process directly and actively interviews, collects, processes data/data analysis, reports, and concludes. This research uses case study research; a case study is carried out in an incentive, detailed and in-depth manner towards an organization or institution. The study results show that The Clinic Beautylosophy Medan applies a participatory leadership style model, as seen from several interviews. Compensation at The Clinic Beautylosophy Medan in the form of direct and indirect compensation. To improve performance at The Clinic Beautylosophy Medan, the leadership style and the provision of compensation, both of which are carried out well by the leadership, make employees enthusiastic in carrying out their duties to achieve organizational goals quickly.